PENGARUH KOMPENSASI, STRESS KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN : (Studi pada Café di Kecamatan Boja Kabupaten Kendal) - Alfina Dwi Khofifah; Andi Kartika (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to test and evaluate the effect of compensation, work stress and work environment on the performance of Café employees located in Boja District, Kendal Regency. The population and sample of the study were all Café employees in Boja District totaling 50 people, selected using the census approach method. This study uses quantitative data with data collection techniques through questionnaires. Data analysis includes validity and reliability tests, multiple linear regression, T test, F test and coefficient of determination (R²) processed using SPSS version 29. The results of the study indicate that compensation has a significant negative effect on employee performance, work stress does not affect employee performance, and the work environment has a significant positive effect on employee performance. Keywords : Compensation, Job Stress, Work Environment, Employee Performance